2021
DOI: 10.30953/tmt.v6.270
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Professionals and Telehealth Usability During COVID-19

Abstract: Objective: During the Coronavirus Disease 2019 (COVID-19) pandemic, many other health providers needed to rapidly adopt telehealth services to ensure continuity of patient care, without the opportunity to extensively evaluate the usability of the adopted technology. Therefore, this study aims to examine health professionals’ telehealth usability during COVID-19 in Florida. Design: This cross-sectional study employed the Telehealth Usability Questionnaire (TUQ) to licensed healthcare providers in Florida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…This is consistent with other studies utilizing the TUQ with a Likert scale with mean scores above the threshold for overall satisfaction. 26,27 Additionally, factors that correlated with greater satisfaction, defined as a TUQ score greater than the overall median J o u r n a l P r e -p r o o f score, were identified based upon age, gender, ethnicity, technology adoption rates, childcare arrangement needs, travel distance and commute time. Surprisingly, underlying comorbidities other than a history of OHT were not associated with significant differences in satisfaction amongst patients, even comparing between groups with zero comorbidities and one or more comorbidities.…”
Section: The Impact Of Descriptive Patient Characteristicsmentioning
confidence: 99%
“…This is consistent with other studies utilizing the TUQ with a Likert scale with mean scores above the threshold for overall satisfaction. 26,27 Additionally, factors that correlated with greater satisfaction, defined as a TUQ score greater than the overall median J o u r n a l P r e -p r o o f score, were identified based upon age, gender, ethnicity, technology adoption rates, childcare arrangement needs, travel distance and commute time. Surprisingly, underlying comorbidities other than a history of OHT were not associated with significant differences in satisfaction amongst patients, even comparing between groups with zero comorbidities and one or more comorbidities.…”
Section: The Impact Of Descriptive Patient Characteristicsmentioning
confidence: 99%
“…Likewise, telemedicine consultations, virtual meetings between professionals, prescription software, monitors and training courses have been some of the technological features which have now been fully embraced by health professionals (Shah et al., 2020; Xu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…19 Davis et al 20 reported that DSME provided by a nurse and dietitian using interactive videoconferencing, telephone, fax and telehealth-enabled retinal camera to patients in the underserved rural community resulted in lower A1c over a 1-year period. 20 In a recent study, Xu et al 21 stated that healthcare professionals reported higher usage, satisfaction and future use of telehealth during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%